Microstructure of amorphous copper-carbon thin films formed by plasma-enhanced chemical vapor deposition; High Temperature Material Processes: An International Quarterly of High-Technology Plasma Processes; Vol. 20, iss. 2 - Astashinskaya M. V. Marina Viktorovna; Astashinsky V. V. Valentin Valentinovich; Kvasov N. T. Nikolay Trafimovich; Uglov V. V. Vladimir Vasilievich (2016, 2016)
Title screen